BEAM CONSTRUCTION IMPACT ANALYSIS BASED ON LIFE CYCLE ASSESSMENT (LCA) USING NETWORK FLOW DIAGRAM - Bernardus Martino; Yatnanta Padma Devia; Indradi Wijatmiko (Rekayasa Sipil, 2021)
Global warming is a problem that happened every year in many various sectors, one of those is construction. Construction projects have a unique character in each construction, therefore it will be difficult if calculating emissions from each construction process. One alternative method that able to calculate carbon dioxide emissions is Life Cycle Assessment. The purpose of this study will discuss the use of the Life Cycle Assessment method on beam products in 216 type house and analyze the CO2 emission load of all beam types. The analysis uses SimaPro software. Results of this research are that from 4 types of beams used in type 216 houses, beam-type 25/50 have the largest percentage of 41.9% and beam-type 15/30 with a percentage of 39.9% of the total CO2 emission of all beam types.